Tinjauan Hukum Informed Consent dalam Kasus Malpraktek dalam Praktek Estetika Studi Kasus Dokter Estetik di Kota Makassar (Analisis Putusan Nomor 441/PID.SUS/2019/PN.MKS) - S. Zulfikar G.Assegaf; AL, Suardi; N, Nur Abdi Fadya H.; Mathius, Denny; Mansyur, Mauluddin; Mutaher, Annisa Anwar (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Malpractice has the potential to harm patients, change the perception of the public, especially patients, and ultimately lead to public demands for doctors to be held accountable for their actions because only certain acts can be punished. One of the malpractice cases that has been examined, decided and heard at the Makassar District Court is decision number 441/Pid.Sus/2019/PN.Mks. In the verdict, the defendant is suspected of having committed malpractice Article 79 letter c of Junto Article 51 letter a of Law of the Republic of Indonesia Number 29 of 2004 concerning Medical Practice and Article 360 paragraph (1) of the Criminal Code. One of the cases that attracted attention was a case involving dr. ES, a doctor who was proven to cause serious harm to patients due to negligence in providing informed consent. This study uses a qualitative approach with case studies to analyze legal decisions taken in malpractice cases. This malpractice case demonstrates the importance of the application of informed consent in any medical procedure, especially in aesthetic practices involving invasive procedures.